2001
DOI: 10.1243/1350650011541800
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and tribological evaluation of metal particle and metal-evaporated tapes in a linear tape drive

Abstract: Improving the performance of computer tape drives is an ongoing process that has recently involved the utilization of metal-evaporated (ME) tapes. The magnetic and tribological performance of the current metal particle (MP) tape and a new dual-magnetic-layer ME tape were evaluated in a Quantum DLT 4000 linear tape drive. Head output, drop-outs and head-tape interface friction were monitored during high-tension (1.7 N) high-speed (4 m=s) short-pass (10 m) shuttling tests without stepping the head. The severe MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Edge-quality measurements were performed using the methodology developed by Topeleski and Bhushan [16], and Goldade and Bhushan [12,14]. Relative edge contour length is used as a measure of edge quality.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Edge-quality measurements were performed using the methodology developed by Topeleski and Bhushan [16], and Goldade and Bhushan [12,14]. Relative edge contour length is used as a measure of edge quality.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…Previously, it has been reported that AME tape has a higher magnetic moment and output signal than MP tape, but its durability has been a concern [3, [6][7][8][9]. Ongoing improvement to AME tape has greatly enhanced the durability of AME tapes and recent studies have shown that positively cupped AME tapes with good initial edge condition will result in durability similar to that of current MP tapes at low tension [10].…”
Section: Introductionmentioning
confidence: 99%
“…The test matrix used for contamination studies also applies to durability (refer to Table 1). For each test, the tape is run for 50,000 cycles where one cycle is shuffling a short length of tape approximately 30 m in length back and forth across the head (Kattner and Bhushan 2000;Topoleski and Bhushan 2001;Ambekar and Bhushan 2003b). The test is commonly referred to as a ''shoeshine'' test where the focus is on tape wear.…”
Section: Durabilitymentioning
confidence: 99%
“…The head-tape interface of a linear tape drive, however, is considerably harsher than that of helical-scan tape drives and, currently, no AME tape is commercially produced for use in a linear tape drive. Topoleski and Bhushan (2001) performed durability tests on ME tapes in a linear tape drive and found that ME tapes were not durable operating against commercial digital linear tape (DLT 4000) heads at the relatively high tension of 0.8 N used in the drive. They reported that the combination of high tension and sharp transverse edges on the head caused removal of the lubricant layer and damage to the coating.…”
Section: Introductionmentioning
confidence: 99%